On interactions, associations, mycetangia, mutualists and symbiotes in insect-fungus symbioses. (April 2020) - Vega, Fernando E.; Biedermann, Peter H.W.
Abstract: There is some confusion in the scientific literature concerning terms involving insect-fungus symbioses, including associations vs. interactions, mycetangia vs. mycangia, symbiote vs. symbiont, and symbiosis vs. mutualism. We present a rationale that demonstrates the difference between an association and an interaction, and why the correct term for exoskeletal cavities that harbor fungi should be mycetangia. In addition, symbiote should be used over symbiont due to its etymology. Precise, common use of terms is important in scientific communication.